Gut microbiota from green tea polyphenol-dosed mice improves intestinal epithelial homeostasis and ameliorates experimental colitis - Wu, Zhenhua; Huang, Shimeng; Li, Tiantian; Li, Na; Han, Dandan; Zhang, Bing; Xu, Zhenjiang Zech; Zhang, Shiyi; Pang, Jiaman; Wang, Shilan; Zhang, Guolong; Zhao, Jiangchao; et al. (Microbiome, 2021)
Background Alteration of the gut microbiota may contribute to the development of inflammatory bowel disease (IBD). Epigallocatechin-3-gallate (EGCG), a major bioactive constituent of green tea, is known to be beneficial in IBD alleviation. However, it is unclear whether the gut microbiota exerts an effect when EGCG attenuates IBD. Results We first explored the effect of oral or rectal EGCG delivery on the DSS-induced murine colitis. Our results revealed that anti-inflammatory effect and colonic barrier integrity were enhanced by oral, but not rectal, EGCG. We observed a distinct EGCG-mediated alteration in the gut microbiome by increasing Akkermansia abundance and butyrate production. Next, we demonstrated that the EGCG pre-supplementation induced similar beneficial outcomes to oral EGCG administration. Prophylactic EGCG attenuated colitis and significantly enriched short-chain fatty acids (SCFAs)-producing bacteria such as Akkermansia and SCFAs production in DSS-induced mice. To validate these discoveries, we performed fecal microbiota transplantation (FMT) and sterile fecal filtrate (SFF) to inoculate DSS-treated mice. Microbiota from EGCG-dosed mice alleviated the colitis over microbiota from control mice and SFF shown by superiorly anti-inflammatory effect and colonic barrier integrity, and also enriched bacteria such as Akkermansia and SCFAs. Collectively, the attenuation of colitis by oral EGCG suggests an intimate involvement of SCFAs-producing bacteria Akkermansia, and SCFAs, which was further demonstrated by prophylaxis and FMT. Conclusions This study provides the first data indicating that oral EGCG ameliorated the colonic inflammation in a gut microbiota-dependent manner. Our findings provide novel insights into EGCG-mediated remission of IBD and EGCG as a potential modulator for gut microbiota to prevent and treat IBD. Video Abstract